Mona’s Cookies Enterprise / Nurul Nazifa Rafarzely - Rafarzely, Nurul Nazifa (2020)
Mona’s Cookies Enterprise offers bakery product and delivery services for customer. We also take an opportunity to provide variety of cookies such as drop cookies and rolled cookies that will give high satisfaction to the customer. Some example we would offer would be something like chewy chocolate chip cookies and lace cookies. We are able to hit the range of target customers through our variety cookies, which will differ depending on the time of day. Due to the foot traffic of our three target consumer markets, we will to be able to open daily except Sunday at 10 am until 10 pm. We will bake our cookies in the onsite pastry kitchen with the baking expertise of our founding partners. All operations will follow procedures to assure that the bakery maintains the highest standards. Main operating procedures for the bakery address food development, purchasing, and customer services.